Prefrontal AMPA receptors are involved in the effect of methylphenidate on response inhibition in rats - ZHANG Dong-dong; ZHANG Yu-qiu; ZHANG Xue-han (Acta Pharmacologica Sinica, 2018)
Abstract Response inhibition is a critical executive control function in many species. Deficits in response inhibition have been observed in many disorders, eg, attention deficit/hyperactivity disorder (ADHD). The stop-signal task (SST) is a unique behavior task for evaluating response inhibition via measuring the covert latency of a stop process, and it is widely used in studies of humans, nonhuman primates and rodents. Methylphenidate (MPH; Ritalin®) is a psychostimulant that is widely used for the treatment of ADHD and that effectively improves response inhibition in individuals with ADHD and normal subjects. However, its mechanism of improving response inhibition remains unknown. In this study we adopted a rodent nose-poking version of the SST to examine response inhibition by estimating the stop signal reaction time (SSRT) in rats. Administration of MPH (1 mg/kg, sc) 25 min before the SST test exerted a baseline-dependent effect of MPH on response inhibition, ie, it shortened the SSRTs only in the rats with larger baseline SSRTs, thereby improving response inhibition in these rats. The effect of MPH on response inhibition remained 3 h after MPH administration. Co-administration of PP2 (1 mg/kg, sc), a Src-protein tyrosine kinase (Src-PTKs) inhibitor that inhibited the upregulation of glutamate receptor expression on the plasma membrane of the prefrontal cortex (PFC), abolished the MPH-caused improvement in response inhibition. Furthermore, intra- PFC infusion of a selective AMPAR antagonist. NASPM (0.3 mmol/L, per side) via stainless guide cannulas implanted earlier abolished the effect of MPH on SSRT. These results suggest that AMPA receptors in the PFC are involved in the effect of MPH on response inhibition in rats.